Dynamic EFL learning application through assemblr EDU for student’s creative writing - arjulayana, Arjulayana; Pujiati, Tri (Englisia Journal, 2025)
Technological advancements hold immense potential for transforming teaching and learning, yet many students struggle to effectively harness digital tools, especially in creative writing. Assemblr EDU (edu.assemblrworld.com), an application that leverages 3D and Augmented Reality (AR) technology, enables users to craft interactive and engaging educational content. Despite its availability as a free resource, a persistent gap in students’ digital literacy prevents them from fully exploiting tools like assemblr EDU for academic purposes. This study explores how assemblr EDU can spark interest in EFL (English as a Foreign Language) learning and elevate learning outcomes. Employing a qualitative descriptive approach, the research involved 38 university students and found that assemblr EDU significantly enhances the development of captivating, interactive learning materials. Students reported that visualizing characters and story elements through the platform made creative writing more enjoyable, effectively bridging the digital literacy divide while cultivating an immersive and motivating learning environment. Ultimately, this approach markedly improves students’ creative writing abilities and overall EFL proficiency.